ISLAM JAWA: PERTAUTAN ISLAM DENGAN BUDAYA LOKAL ABAD XV - Ulum, Bahrul; Mufarrohah (LPPI Universitas Al-Qolam Malang, 2014)
On the other hand, Islam emphasizes on equality, justice, takÄful, freedom and honor, and has theocentrism humanistic concept as a core value of all its teachings. Therefore, it is always interesting to explore the Â development of Islamic civilization. At the same time, in translating the concept of the sky to the earth, Islam has dynamic character, elastic and accommodating the local culture, as long as not contrary to the principles of Islam itself. The problem only lies in the procedures and technical implementation. In the context of Indonesian Islamic propaganda, its spread is never separated from the role of Wali Songo. This wali, although many people believed that their mission is much influenced by Sufism thought, but that does not mean they do not consider other aspects, such as geo-strategy, geo-politics, socio-cultural and others. The relationship between Islam and local issues is a never ended thrill. The intimate connection between the two is triggered by excitement followers of Islam who believe in religion with the slogan: shÄlih li kull zamÄn wa makÄn. In this regard, it is reasonable attempt to reconcile between religion and culture. Demak Mosque is a concrete example of the attempt of reconciliation or the accommodation. Islamic way of greeting the local culture is to change the substance of particular locality towards universal-religious as can be seen in the process of Islamization puppet by giving nuances of symbolic-religious character of Islamization than Arabization. Keywords: Islam-Java, acculturation of Islam, local culture